(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2013)
The aggregation of Amyloid beta peptides is considered as one of the causative events in the pathogenesis of Alzheimer’s disease (AD). Polyphenols present in different plant sources, which have acclaimed therapeutic values, are known to inhibit the formation of Amyloid fibrils. Hence, docking studies with different polyphenols were carried out to appreciate their binding modes and plausible molecular interactions. The results reveal a consensus pattern of association, exhibiting that all the ligands preferentially dock to the metal coordinating residues in the peptide fragments. In fact, the metal interacting geometries in the Aβ segments are known to be implicated in aggregation events. Further, due to non-specific binding, these polyphenols are expected to have a competitive inhibitory efficacy over a range of amyloid peptide fragments. Thus, these findings suggest that the polyphenolic compounds could become promising lead molecules that aid in the development of inhibitors and neuroprotectors towards prevention of amyloid fibril formations and AD.